PENGARUH TERAPI MUSIK TERHADAP CEMAS PASCA OPERASI PADA PASIEN BEDAH JANTUNG: PENERAPAN EVIDENCE BASED NURSING (EBN) - Dinny Atin Amanah; Elly Nurachmah; Tuti Herawati; Hermin Esti Dianingtyas (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2026)
Cardiovascular disease is a leading cause of mortality and morbidity worldwide and constitutes a major global burden. One proven effective treatment for cardiovascular disease is heart surgery, but patients often experience anxiety and depression both preoperatively and postoperatively. Unmanaged anxiety and depression in the postoperative period can negatively impact patient recovery. An intervention that nurses can implement to address anxiety is music therapy. This study aimed to prove the effect of music therapy on postoperative anxiety and depression in heart surgery patients. This study used a quantitative quasi-experimental research design with a two-group (non-equivalent) pretest-posttest control group design. Researchers divided respondents into two groups: the music therapy group and the control group. Respondents from both groups completed a questionnaire before being given the intervention. Respondents in the music therapy group were given classical music intervention twice, approximately 2 hours after post-extubation and the following day. Meanwhile, the control group was given routine room care intervention, namely deep breathing. The study sample consisted of 28 respondents in each group. Anxiety assessment was carried out using the Indonesian version of the Hospitalized Anxiety and Depression Scale (HADS). The results of the statistical test of the difference in mean anxiety and depression scores after both the first and second interventions between the intervention group and the control group using the Independent T-Test showed a significant difference (p<α; α = 0,05). These results indicate that there is an effect of music therapy on postoperative anxiety and depression in cardiac surgery patients. Music therapy can reduce postoperative anxiety and depression in cardiac surgery patients.